2012
DOI: 10.1177/2048872612453924
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the predictive validity of three contemporary bleeding risk scores in acute coronary syndrome

Abstract: Of contemporary bleeding RS, the CRUSADE score was found to be the most accurate quantitative tool for NSTEACS and STEMI patients undergoing coronary arteriography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 27 publications
(52 reference statements)
3
27
0
3
Order By: Relevance
“…Among the risk scores explored, we found CRUSADE to have a better predictive profile for major bleeding compared with HAS‐BLED and a similar profile compared to ACUITY. This observation is consistent with some previous studies and with the European Society of Cardiology guidelines that recommended the CRUSADE score for bleeding risk stratification in non–ST‐segment elevation MI 9, 15, 16. It might be speculated that the set of covariates used to predict bleeding risk for the CRUSADE score better reflects the bleeding risk in patients undergoing stent implantation and subsequent DAPT.…”
Section: Discussionsupporting
confidence: 91%
“…Among the risk scores explored, we found CRUSADE to have a better predictive profile for major bleeding compared with HAS‐BLED and a similar profile compared to ACUITY. This observation is consistent with some previous studies and with the European Society of Cardiology guidelines that recommended the CRUSADE score for bleeding risk stratification in non–ST‐segment elevation MI 9, 15, 16. It might be speculated that the set of covariates used to predict bleeding risk for the CRUSADE score better reflects the bleeding risk in patients undergoing stent implantation and subsequent DAPT.…”
Section: Discussionsupporting
confidence: 91%
“…18 Amador et al first suggested that both ischaemic and bleeding risk scores could be used to predict in-hospital mortality, isch- In conclusion, the results of this study support previous findings on the superiority of the GRACE vs the CRUSADE score to predict in-hospital mortality in ACS patients, and adds to the growing evidence that this score might also serve the needs to predict bleeding complications. 18 Amador et al first suggested that both ischaemic and bleeding risk scores could be used to predict in-hospital mortality, isch- In conclusion, the results of this study support previous findings on the superiority of the GRACE vs the CRUSADE score to predict in-hospital mortality in ACS patients, and adds to the growing evidence that this score might also serve the needs to predict bleeding complications.…”
Section: Plications In Stemi and Nste-acs Compared With Action-andsupporting
confidence: 87%
“…AUC, area under the curve GRACE Score and enrolled 13 686 Canadian ACS patients from 1999-2008. Current guidelines recommend the use of the CRUSADE score for bleeding risk stratification 8,18,19. They concluded that the number of risk factorsdoes not enhance the prognostic value over the validated GRACE risk score 15.…”
mentioning
confidence: 99%
“…1 The Mehran bleeding score is straightforward to calculate, encompasses several clinical and biochemical parameters, and has been validated in several studies. 7,8 In the present study, the average Mehran bleed score was significantly higher in patients treated with warfarin. The predicted risk of 30 days of the patient in the very high bleed score category (38% of the patients treated with warfarin score >20) is 10%.…”
Section: Discussionmentioning
confidence: 85%
“…6 As with other studies, we modified this slightly by excluding periprocedural anticoagulant therapy. 7 It is important to note that the Mehran bleed score does not include baseline use of warfarin. For SYNTAX score calculation, an on-line calculator was used (http://ir-nwr.ru/ calculators/syntaxscore.htm).…”
Section: Methodsmentioning
confidence: 99%